Inhibition of Phospholipase A2 by Dihydrostilbene Glycoside Isolated from the Ethyl Acetate Fraction of Indigofera capitata: Structural Insights from IR and NMR - Dauda, Maryam Mahmud; Dauda, Garba; Abdullahi, Sakynah Musa; sada, Hadiza; Sule, Mohammed Ibrahim; Hassan, Halimatu Sadiya; Musa, Aliyu Muhammad (Sciences of Phytochemistry, 2025)
Snakebites and subsequent envenomations remain a significant health challenge, especially in rural regions of underdeveloped countries, where they contribute to high mortality rates. In Nigeria, particularly in rural areas, the scarcity of healthcare facilities and antivenoms exacerbates the issue. Rural communities commonly seek traditional plant-based remedies due to their affordability and cultural significance. This study investigates the ethyl acetate fraction of Indigofera capitata, a plant traditionally used to treat snakebites, for its potential to inhibit phospholipase A2 (PLA2) activity. Chromatographic separation of the ethyl acetate fraction led to the isolation of a greenish solid substance, coded MM2, identified as 3-methoxyl, 5, 4', 5' trihydroxyl, 6' pentyl-4-O-glycopyranoside through chromatographic and spectroscopic methods. The inhibition of PLA2 was assessed using an in vitro acidimetric assay. Compound MM2 was tested at 1 mg/mL, 0.1 mg/mL, and 0.01 mg/mL. The highest inhibition of 47.37% was observed at 1 mg/mL. At 0.1 mg/mL, the inhibition decreased to 36.84%, indicating reduced efficacy. Interestingly, at 0.01 mg/mL, the inhibition returned to 47.37%, suggesting that the enzyme inhibition by MM2 is concentration-independent within the tested range. The promising PLA2 inhibition observed with compound MM2 supports its potential as an antivenom agent. This research highlights the therapeutic potential of I. capitata in addressing the global snakebite crisis. To the best of our knowledge, this is the first report documenting this compound's isolation, characterization, and antivenin screening.